2017
DOI: 10.1371/journal.pone.0188635
|View full text |Cite
|
Sign up to set email alerts
|

The validity of linear and non-linear heart rate metrics as workload indicators of emergency physicians

Abstract: BackgroundIt has been shown that linear and non-linear heart rate variability (HRV) metrics are suitable to assess workload of anesthetists administering anesthesia. In pre-hospital emergency care, these parameters have not yet been evaluated. We hypothesized that heart rate (HR) and HRV metrics discriminate between differing workload levels of an emergency physician.MethodsElectrocardiograms were obtained from 13 emergency physicians. Mean HR, ten linear and seven non-linear HRV metrics were analyzed. For eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 39 publications
1
48
0
2
Order By: Relevance
“…Parts of the results, specifically the results regarding the validity of linear and non-linear HRV metrics, have been published earlier. [ 15 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parts of the results, specifically the results regarding the validity of linear and non-linear HRV metrics, have been published earlier. [ 15 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 9 ] In addition to heart rate itself (mean HR),[ 9 11 ] heart rate variability (HRV) metrics have been shown to quantify workload in experimental settings and under real-life circumstances. [ 9 , 12 15 ] Among these, the non-linear HRV metric Permutation Entropy (PeEn) has been found to be a sensible correlate of workload in anesthetists providing general anesthesia. [ 9 ] Our recent work indicated that non-linear HRV metrics can also distinguish workload levels during pre-hospital emergency care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have compared linear and nonlinear HRV metrics (Francesco et al, 2012;Schneider et al, 2017;H. Young & Benton, 2015).…”
Section: Background and Motivationmentioning
confidence: 99%
“…The majority, however, have been related to HRV analysis in clinical diagnosis (Francesco et al, 2012). A smaller number of studies have assessed the relative utility of these methods as compared to time and frequency domain methods in mental MWL research (Heine et al, 2017;Schneider et al, 2017;H. Young & Benton, 2015).…”
Section: Background and Motivationmentioning
confidence: 99%